Discovery of Common Putative Drug Targets and Vaccine Candidates for Mycobacterium tuberculosis sp.: drug discovery and vaccine candidates identification of M. tb - Nalamolu, Ravina Madhulitha; Pasala, Chiranjeevi; Katari, Sudheer Kumar; Amineni, Umamaheswari (Journal of Drug Delivery and Therapeutics, 2019)
ABSTRACT Mycobacterium tuberculosis is the bacteria that cause tuberculosis (TB), an infection that usually affects the lungs and can be fatal without proper treatment. Combating through available drugs became a difficult task due to drug resistance and lack of appropriate common targets against genetically diverse strains. Since to improve efficacy, the effective targets should be identified and critically assessed. In the study, we aim to predict the potential novel targets against M. tuberculosis strains by employing in silico approach. The complete proteomic datasets of 23 M. tuberculosis strains was comparatively processed by executing R-scripts and eventually predicted 3906 ’conserved gene products’. Further, we performed subtractive proteomic approach in search of promising crucial targets. Consequently, eight enzymes and two membrane proteins were prioritized as new therapeutic and vaccine targets respectively which found to have more interactors in network with high-confidence score, druggability and antigenicity. Therefore, outcomes of the study emphasize the importance of new targets may counteract with false-positive/negatives and facilitate appropriate potential targets for a new insight of reliable therapeutic development. Key words: Mycobacterium tuberculosis, Multidrug resistance tuberculosis and Extensive drug resistant tuberculosis.